Personal data protection as an element of the right to privacy - Suduł, Przemysław; Piękoś, Dominik (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Privacy is one of the most important values for any human being, and the right to privacy is particularly strongly linked to the protection of human dignity. Throughout the history of the world, people have always shown an interest in the affairs of others. In the modern world, in an era of widespread technological advances that allow the collection, gathering and retrieval of information about others, the need for legal protection of the human right to privacy is increasing. In this regard, it is necessary to delineate and guarantee the spheres of personal life belonging to each person, in which no unauthorized person shall interfere. Every human being has the right to dispose of himself or herself, the right to undisturbed development of his or her own physical and psychological identity, and thus to live his or her own life, shaped according to his or her own will and independent to a certain extent from external influences.